A multi-step approach to the treatment of giant scalp congenital hemangiomas: a report of two cases - Ho, Raymond W.; Nonnenmacher, Gabriel; Henkes, Hans; Vokuhl, Christian; Loff, Steffan (Frontiers in Surgery, 2023)
This is a review of two cases of neonatal giant scalp congenital hemangioma. Both patients were treated with propranolol using a similar multi-step approach that included transarterial embolization of the supplying arteries followed by surgical resection of the lesion. In this report, we discuss the treatments, complications, and clinical outcomes of interventions and surgical procedures.